IMPLEMENTASI SENSOR SEMIKONDUKTOR SEBAGAI ROBOT PENDETEKSI KEBOCORAN GAS - Rouhillah; Zoel Fachri; Zaki Akbar (J-Innovation, 2018)
Hazardous gas detection robot using semiconductor sensor is aimed to help operators high risk jobs. This harmful gas detector robot using RF Wireless is able to detect gas leaks by using the semiconductor sensor such as MQ2 sensors. Robot use the LCD to display the presence or absence of gas detected by the MQ2, and a buzzer as the alarm if gas is detected. The advantage of this robot is the robot can detect locations of gas that can’t be reached by humans. The robot is controlled by using a joystick which data is sent by NRF24L01transmiter with maximum distance ±100 meter, so it helps people in the finding of a gas leak location process.